From DNA Damage to Cancer Progression: Potential Effects of Cytolethal Distending Toxin - Lai, Yi-Ru; Chang, Yu-Fang; Ma, Jason; Chiu, Cheng-Hsun; Kuo, Ming-Ling; Lai, Chih-Ho (Frontiers in Immunology, 2021)
Cytolethal distending toxin (CDT), one of the most important genotoxins, is produced by several gram-negative bacteria and is involved in bacterial pathogenesis. Recent studies have shown that bacteria producing this peculiar genotoxin target host DNA, which potentially contributes to development of cancer. In this review, we highlighted the recent studies focusing on the idea that CDT leads to DNA damage, and the cells with inappropriately repaired DNA continue cycling, resulting in cancer development. Understanding the detailed mechanisms of genotoxins that cause DNA damage might be useful for targeting potential markers that drive cancer progression and help to discover new therapeutic strategies to prevent diseases caused by pathogens.